A systematic review of factors affecting adherence to malaria chemoprophylaxis amongst travellers from non-endemic countries - Ahluwalia, Julian (Malar J, 2020)
BACKGROUND: The aim of this systematic review was to identify predictors of actual or intended adherence with malaria chemoprophylaxis amongst travellers from non-endemic countries visiting endemic countries. METHODS: A systematic review of the literature was conducted using MEDLINE, Embase, PsycINFO and Global Health databases for studies published up to April 2019. Studies were included if they assessed reasons for adherence among people travelling from a country where malaria was not endemic to a country where it was. RESULTS: Thirty-two studies were included. Predictors of adherence were categorized as relating to either the nature of the travel or the traveller themselves. The three main predictors associated with nature of travel included: destination (e.g. country visited, urban vs rural areas), length of travel and type of travel (e.g. package vs backpacking holiday). The four main traveller-associated predictors were: age, reason for travel (e.g. business, leisure or visiting friends and relatives), perceived risk of catching malaria and experienced or expected medication effects. CONCLUSIONS: In order to improve adherence, clinicians should focus on travellers who are least likely to exhibit adherent behaviour. This includes travellers visiting destinations known to have lower adherence figures (such as rural areas), backpackers, business travellers, younger travellers and those travelling for longer periods of time. They should also check to ensure travellers’ perceptions of the risks of malaria are realistic. Where appropriate, misperceptions (such as believing that curing malaria is easier than taking prophylaxis or that travellers visiting relatives have some level of innate immunity) should be corrected. All travellers should be informed of the potential side-effects of medication and given guidance on why it is nonetheless beneficial to continue to take prophylaxis. Further research is required to test interventions to improve adherence.